Effects of arginase genetic polymorphisms on nitric oxide formation in healthy pregnancy and in preeclampsia - Pinto-Souza, Caroline C. [UNESP]; Coeli-Lacchini, Fernanda; Luizon, Marcelo R.; Cavalli, Ricardo C.; Lacchini, Riccardo; Sandrim, Valeria C. [UNESP] (Elsevier, 2021)
Background and aims: Preeclampsia is associated with reduced nitric oxide (NO) bioavailability. Arginase is related to NO synthesis, but relatively unexplored in preeclampsia. However, no previous study has examined whether variations in ARG1 and ARG2 genes affect NO bioavailability and the risk of preeclampsia. Here, we compared the alleles and genotypes of single nucleotide polymorphisms (SNPs) in ARG1 (rs2781659; rs2781667; rs2246012; rs17599586) and ARG2 (rs3742879; rs10483801) in healthy pregnant women and preeclampsia, and examined whether these SNPs affect plasma nitrite concentrations (a marker of NO formation) in these groups. Methods: Genotypes for the ARG1 and ARG2 SNPs were determined by Taqman probe and plasma nitrite by an ozone-based chemiluminescence assay. Results: Regarding ARG1 SNPs, the GG genotype and G allele frequencies for rs2781659, and the C allele frequencies for rs2246012 were higher in preeclampsia compared to healthy pregnant women. Moreover, the GG genotype for rs2781659 and the TT genotype for rs2781667 were associated with higher plasma nitrite in healthy pregnant. We found no association of ARG2 polymorphisms with preeclampsia or nitrite levels in the study groups. Conclusions: Our results suggest that SNPs of ARG1 increase the risk of preeclampsia and modulate plasma nitrite levels in healthy pregnant women.
Keywords: Arginase; Genetic polymorphisms; Nitric oxide; Nitrite; Preeclampsia; Pregnancy